Hard-to-Measure Goods and Services : Essays in Honor of Zvi Griliches - Berndt, Ernst R.; Hulten, Charles R. (Studies in income and wealth, 2007)
The celebrated economist Zvi Griliches's entire career can be viewed as an attempt to advance the cause of accuracy in economic measurement. His interest in the causes and consequences of technical progress led to his pathbreaking work on price hedonics, now the principal analytical technique available to account for changes in product quality. Hard-to-Measure Goods and Services, a collection of papers from an NBER conference held in Griliches's honor, is a tribute to his many contributions to current economic thought. Here, leading scholars of economic measurement address issues in the areas o.